Optimization of Tubular Solar Distillation Performance With Nano-PCM and Parabolic Trough Collector - Seftian Amanda, Muhammad; Amin, Muhammad; Azuar Rizal, Teuku (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
Solar distillation is a desalination method that utilizes solar energy to convert saline water into freshwater. However, the efficiency of this process is often limited by temperature fluctuations and low heat storage capacity. Phase Change Material (PCM) has been used as a thermal storage medium in solar distillation systems, but the low thermal conductivity of pure PCM remains a major challenge. To address this limitation, this study incorporates graphene carbon nanoparticles into beeswax-based PCM to enhance its thermal properties. This research examines the effect of adding 0.3% graphene to beeswax PCM on the performance of a tubular solar distillation system equipped with a Parabolic Trough Collector (PTC). The experiment compares the performance of pure PCM and nano-PCM, each weighing 90 grams and enclosed in an aluminum foil bag. The experimental results indicate that the addition of graphene to beeswax PCM improves solar distillation performance based on three key parameters, namely temperature, productivity, and efficiency. Nano-PCM achieved a maximum temperature of 76 °C, representing a 2.7% increase compared to pure PCM. In terms of productivity, the distilled water yield of nano-PCM was recorded at 0.834 L/m² on October 15, 2024, and 0.819 L/m² on October 17, 2024, marking an increase of 3.22% and 6.64%, respectively, compared to pure PCM. Furthermore, the system’s efficiency also improved with an increase of 3.03% on October 15, 2024, and 6.7% on October 17, 2024. Overall, this study demonstrates that the use of nano-PCM enhances the performance of solar distillation, particularly in terms of operating temperature, water productivity, and system efficiency. These findings highlight the significant potential of nano-PCM applications in large-scale solar distillation systems to improve freshwater production efficiency.